Stable double spacing multiwavelength Brillouin-Erbium doped fiber laser based on highly nonlinear fiber - Ahmad, B.A.; Al-Alimi, A.W.; Abas, Ahmad Fauzi; Harun, Sulaiman Wadi; Mahdi, Mohd Adzir (IOP Publishing, 2012)
A double frequency spaced multiwavelength Brillouin-Erbium doped fiber laser (BEDFL) with figure-of-eight cavity have been successfully developed and tested. Double frequency spacing is achieved by using a piece of 2 km of highly nonlinear fiber (HNLF) as a gain medium. Figure-of-eight configuration removes the odd order Stokes signals via a four-port circulator. Fifteen Stokes channels are simultaneously generated with a spacing of 0.154 nm that is around 20 GHz, when the Brillouin pump and 980 nm pump powers are fixed at the optimized values of 6 dBm and 40 mW, respectively. Fourteen anti stoke channels are also obtained, which are generated through four wave mixing (FWM) process in the laser cavity. The output is smooth triangular comb. The BEFL can also be tuned from 1526.5 to 1567.5 nm.